2017
DOI: 10.1002/hep.29462
|View full text |Cite|
|
Sign up to set email alerts
|

Taurine up‐regulated gene 1 functions as a master regulator to coordinate glycolysis and metastasis in hepatocellular carcinoma

Abstract: Cancer cells display altered glucose metabolism characterized by a preference for aerobic glycolysis. The aerobic glycolytic phenotype of hepatocellular carcinoma (HCC) is often correlated with tumor progression and poorer clinical outcomes. However, the issue of whether glycolytic metabolism influences metastasis in HCC remains unclear. In the current study, we showed that knockdown of taurine up-regulated gene 1 (TUG1) induces marked inhibition of cell migration, invasion, and glycolysis through suppression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
101
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 42 publications
0
101
0
2
Order By: Relevance
“…To sum up, these date manifested a tumorigenic gene role of TUG1 in HCC. A previous study reported that knockdown of TUG1 markedly retarded cell growth, metastasis and glycolysis in HCC [28]. This implied that TUG1 might regulate other behaviors of HCC cells, which requires further study.…”
Section: Discussionmentioning
confidence: 92%
“…To sum up, these date manifested a tumorigenic gene role of TUG1 in HCC. A previous study reported that knockdown of TUG1 markedly retarded cell growth, metastasis and glycolysis in HCC [28]. This implied that TUG1 might regulate other behaviors of HCC cells, which requires further study.…”
Section: Discussionmentioning
confidence: 92%
“…The liver microenvironment is naturally more conducive to cells that display a high glycolytic profile and are adapted for a low-oxygen state. This is illustrated by the abundance of studies demonstrating that primary hepatocellular carcinomas preferentially engage in glycolytic metabolism to proliferate in the liver (Jiao et al, 2017; Lin et al, 2017; Song et al, 2015). It is therefore tempting to speculate that to colonize the liver, metastasizing cancer cells from other organs must be able to overcome this hypoxic barrier in order to adapt to the hepatic environment.…”
Section: Liver Metastases: Competing For Resourcesmentioning
confidence: 99%
“…These extensive connections between cancer metabolism and aggressive cancer features suggest that targeting metabolic pathways may be a promising effective method for treating cancer patients. Recent research demonstrated that cancer metabolism reprogramming can be regulated by both coding and noncoding genes via targeting glycolysis‐related transporters, enzymes and signalling pathways (Cairns et al , 2011; Lin et al , 2018; Yang et al , 2014). A previous study and our recent publication demonstrated that a key glycolytic transporter, glucose transporter 1 (GLUT1), is specifically overexpressed in HCC and promotes HCC cell glycolysis and progression (Amann et al , 2009; Shang et al , 2017).…”
Section: Introductionmentioning
confidence: 99%